When Did the Greeks Abandon Ai Khanoum? - Holt, Frank L. (Anabasis. Studia Classica et Orientalia, 2012)
Over the past thirty years or so, most scholars have accepted the numismatic and epigraphic evidence for dating the end of Greek rule at Aï Khanoum during or immediately after the reign of Eucratides I (ca. 170–145 BCE). This consensus, however, is not absolute and it remains desirable that all archaeological data be reassessed from time to time in the interests of scientific progress. Thus, Awadh K. Narain has tentatively offered a dissenting view that could possibly date the abandonment of Aï Khanoum as many as fourteen years later (ca. 131 BCE). Recently, Jeffrey Lerner has argued for a more radical chronological shift that would place the end of Greek control over Aï Khanoum almost a century later (ca. 50 BCE). As I have noted elsewhere, Lerner’s theory poses a fascinating challenge to the status quo and warrants a close testing of the author’s thesis and methodology. The following analysis, which focuses on the numismatic arguments presented by Lerner and to some extent by Narain as well, is offered here as a tribute to our mutual friend Dr. Vadim M. Masson, accomplished numismatist and distinguished Academician of the Russian Academy of Sciences. Professor Masson always paid close attention to coin finds and their chronological implications, so this paper contributes to one of his key areas of interest. Whatever the merits of other kinds of evidence, numismatic data sets the chronological limits for the Greek abandonment of Aï Khanoum around the middle of the second century BCE. Thus, the status quo ante prevails: If Eucratides I was not the last Greek king to govern the city, one of his near contemporaries surely was.